Hubungan Pengetahuan dan Perilaku Masyarakat dengan Keberadaan Jentik Nyamuk - Tati Tati Ruhmawati (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2017)
ABSTRACT: Environment-based disease is a health problem, one of them is dengue hemorrhagic disease (DHF). In Cimahi Region, the number of case of DHF is tend to increasing each year. The research purpose is to know the relation between knowledge, attitude and behavior of the community with the existence of mosquito’s larvae in RW 06 Pasirkaliki, North Cimahi. Research hypothesis shows that the is correlation between knowledge and behavior of community with the existence of mosquito’s larvae. The population are all of the head of family (KK)in RW 06 Pasirkaliki, North Cimahi which is reached up to 260 KK. The sample taken (42 KK) from population using simple random sampling technique. Type of observational analytic research with cross sectional design. Data collection technique by interview and observation. The data then analysed using chi square method. Research result shows that there is correlation between knowledge and behaviour of the community with the existence of mosquito’s larvae which is p value for knowledge 0,0031 and p value for behavior 0,000 at α 0,05. Keywords: Knowledge, Behavior, Mosquito larvae